ANALISIS KEBUTUHAN TERMINAL AGROPOLITAN DI KABUPATEN GOWA - Usman, Khairul Sani (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2015)
Gowa is one area that has a high potential in the agricultural sector . As one support agricultural development of the area needed a tool that can serve as a place to accommodate and distribution of agricultural goods, especially in rural areas can then add value to agricultural products so as to increase local revenues in Gowa. But in fact in Gowa is not available a facility that can accommodate and distribution of agricultural goods . Marketing activities and unloading of agricultural products are generally often take place in locations traditional markets and partly carried out at several locations that are not on the allotment, as in Jalan Poros Pallangga - Limbung the course of an arterial road function. Who every day experience the congestion caused by these activities. Based on the above issues will be carried out through research that this study is " Needs Analysis Terminal Agro in Gowa ". The aim of this study is to determine the needs and development of Agro Terminal in Gowa. The method of approach used in this study is descriptive. From the analysis we found that As one of the region support the development of Agriculture then it should be in Gowa has Terminal Agro. The Agro terminal function and acts as a central collection and distribution of agricultural potential in each region Agropolitan more targeted and effective as a center for buying and selling agricultural commodities, which in turn will improve the quality and quantity of production are likely to be developed by the public or that can trigger proper allocation of new investments on activities based Agropolitan.